Nigeria : Experience with Structural Adjustment. (Occasional Papers; Occasional Paper, 1997)
Over the past two decades, Nigeria has not reaped fully the benefits of its national wealth despite its efforts at structural adjustment. This paper concludes that the facts do not justify the negative image that structural adjustment has had in Nigeria. Vigorous market reforms and tight financial policies had resulted in economic growth and employment expansion, but they were abandoned too soon to have sustained benefits.